2008
DOI: 10.1029/2008gl035143
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of variability and trends of extreme rainfall events over India using 104 years of gridded daily rainfall data

Abstract: [1] In this study, using 104 years (1901 -2004) of high resolution daily gridded rainfall data, variability and long-term trends of extreme rainfall events over central India have been examined. Frequency of extreme rainfall events shows significant inter-annual and inter-decadal variations in addition to a statistically significant long term trend of 6% per decade. Detailed analysis shows that inter-annual, inter-decadal and long-term trends of extreme rainfall events are modulated by the SST variations over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
371
1
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 573 publications
(394 citation statements)
references
References 22 publications
17
371
1
5
Order By: Relevance
“…It has been shown by Rajeevan et al (2008) that surface water vapour content and surface mean wind speeds are increasing significantly over the ocean during monsoon season causing increase in the evaporation flux from the ocean surface and more moisture availability, and this may result in an increase in the number of extreme events.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown by Rajeevan et al (2008) that surface water vapour content and surface mean wind speeds are increasing significantly over the ocean during monsoon season causing increase in the evaporation flux from the ocean surface and more moisture availability, and this may result in an increase in the number of extreme events.…”
Section: Discussionmentioning
confidence: 99%
“…Heavy precipitation events during critical phases of crop growth may adversely affect foodgrains. However, an increase in heavy precipitation activities is observed over India in recent years (Rajeevan et al 2008). A study, using high-resolution gridded rainfall data for a period from 1951 to 2003, revealed that the frequency and magnitude of extreme rainfall events are increasing, while moderate events are decreasing over central India during summer monsoon (Goswami et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The severe rains have a substantial socio-economic impact in tropical areas which are dependent on agriculture and prone to natural hazards such as flooding and mass movements. Thus, in recent decades in India, many authors have analysed extreme rainfall series for periods of different lengths, using data from different rain-gauge networks and a variety of methods (Rakhecha and Soman 1994;Dhar and Nandargi 1995;Roy and Balling 2004;Goswami et al 2006;Rajeevan et al 2008;Guhathakurta et al 2011).…”
Section: Introductionmentioning
confidence: 99%